The effect of albumin and γ-globulin on synovial fluid lubrication: Implication for knee joint replacements - Nečas, D; Sadecká, K; Vrbka, M; Galandáková, A; Wimmer, M A; Gallo, J; Hartl, M (Journal of the mechanical behavior of biomedical materials, 2021)
Total knee arthroplasty has become a routine procedure for patients suffering from joint diseases. Although the number of operations continuously increases, a limited service-life of implants represents a persisting challenge for scientists. Understanding of lubrication may help to suitably explain tribological processes on the way to replacements that become durable well into the third decade of service. The aim of the present study is to assess the formation of protein lubricating film in the knee implant. A developed knee simulator was used to observe the contact of real femoral and transparent polymer tibial component using fluorescent microscopy. The contact was lubricated by various protein solutions with attention to the behaviour of albumin and γ-globulin. In order to suitably mimic a human synovial fluid, hyaluronic acid and phospholipids were subsequently added to the solutions. Further, the change in shape and the migration of the contact zone were studied. The results showed considerable appearance differences of the contact over the swing phase of the simplified gait cycle. Regarding film formation, a strong interaction of the various molecules of synovial fluid was observed. It was found that the thickness of the lubricating layer stabilizes within around 50 s. Throughout the contact zone, protein agglomerations were present and could be clearly visualised using the applied optical technique.
Keywords: Humans; Arthroplasty, Replacement, Knee; Albumins; Knee Joint; totální endoprotéza kolene; synoviální tekutina; Synovial Fluid; lubrikace; albuminy; gama-globuliny; kolenní kloub; Lubrication; lidé; gamma-Globulins